Addressing Europe's democratic deficit: An experimental evaluation of the pan-European district proposal. (December 2016) - Bol, Damien; Harfst, Philipp; Blais, André; Golder, Sona N; Laslier, Jean-François; Stephenson, Laura B; Van der Straeten, Karine
Many academics and commentators argue that Europe is suffering from a democratic deficit. An interesting proposal that has been put forward to address this problem is to elect some members of the European parliament in a pan-European district. In this article, we evaluate this proposal using an online experiment, in which thousands of Europeans voted on a pan-European ballot we created. We find that the voting behaviour of European citizens would be strongly affected by the presence or absence of candidates from their own country on the lists. If a pan-European district is created, our findings provide an argument in favour of using a closed-list ballot and establishing a maximum number of candidates from each country on the lists.